Assessment of EnMAP data quality through global product validation activities - Maximilian Brell; Philipp Reiners; Luis Guanter; Karl Segl; Sabine Chabrillat; Daniel Scheffler; Mariana A. Soppa; Niklas Bohn; Javier Gorrono; Alexander Kokhanovsky; Astrid Bracher; Martin Bachmann; et al. (Remote Sensing of Environment, 2026)

Electron transfer of extremophiles in bioelectrochemical systems - Miriam Edel; Laura-Alina Philipp; Jonas Lapp; Johannes Reiner; Johannes Gescher (Extremophiles, 2022)
The interaction of bacteria and archaea with electrodes is a relatively new research field which spans from fundamental to applied research and influences interdisciplinary research in the fields of microbiology, biochemistry, biotechnology as well as process engineering. Although a substantial understanding of electron transfer processes between microbes and anodes and between microbes and cathodes has been achieved in mesophilic organisms, the mechanisms used by microbes under extremophilic conditions are still in the early stages of discovery. Here, we review our current knowledge on the biochemical solutions that evolved for the interaction of extremophilic organisms with electrodes. To this end, the available knowledge on pure cultures of extremophilic microorganisms has been compiled and the study has been extended with the help of bioinformatic analyses on the potential distribution of different electron transfer mechanisms in extremophilic microorganisms.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Microbial communities and residues in robinia- and poplar-based alley-cropping systems under organic and integrated management - Hanyin Sun; Philipp Koal; Georg Gerl; Reiner Schroll; Andreas Gattinger; Rainer Georg Joergensen; Jean Charles Munch (Agroforestry Systems, 2018)

First year of practical experiences of the new Arctic AWIPEV-COSYNA cabled Underwater Observatory in Kongsfjorden, Spitsbergen - Philipp Fischer; Max Schwanitz; Reiner Loth; Uwe Posner; Markus Brand; Friedhelm Schröder (Ocean Science, 2017)
A combined year-round assessment of selected oceanographic data and a macrobiotic community assessment was performed from October 2013 to November 2014 in the littoral zone of the Kongsfjorden polar fjord system on the western coast of Svalbard (Norway). State of the art remote controlled cabled underwater observatory technology was used for daily vertical profiles of temperature, salinity, and turbidity together with a stereo-optical assessment of the macrobiotic community, including fish. The results reveal a distinct seasonal cycle in total species abundances, with a significantly higher total abundance and species richness during the polar winter when no light is available underwater compared to the summer months when 24 h light is available. During the winter months, a temporally highly segmented community was observed with respect to species occurrence, with single species dominating the winter community for restricted times. In contrast, the summer community showed an overall lower total abundance as well as a significantly lower number of species. The study clearly demonstrates the high potential of cable connected remote controlled digital sampling devices, especially in remote areas, such as polar fjord systems, with harsh environmental conditions and limited accessibility. A smart combination of such new digital sampling methods with classic sampling procedures can provide a possibility to significantly extend the sampling time and frequency, especially in remote and difficult to access areas. This can help to provide a sufficient data density and therefore statistical power for a sound scientific analysis without increasing the invasive sampling pressure in ecologically sensitive environments.

Large-scale genetic census of an elusive carnivore, the European wildcat (Felis s. silvestris) - Katharina Steyer; Robert H. S. Kraus; Thomas Mölich; Ole Anders; Berardino Cocchiararo; Christiane Frosch; Alexander Geib; Malte Götz; Mathias Herrmann; Karsten Hupe; Annette Kohnen; Matthias Krüger; et al. (Conservation Genetics, 2016)

A mesocosm experiment investigating the effects of substratum quality and wave exposure on the survival of fish eggs - Stefan Stoll; Wolfgang Nikolaus Probst; Reiner Eckmann; Philipp Fischer (Aquatic Sciences, 2010)

Lake water level increase during spring affects the breeding success of bream Abramis brama (L.) - Wolfgang Nikolaus Probst; Stefan Stoll; Lars Peters; Philipp Fischer; Reiner Eckmann (Hydrobiologia, 2009)